Partial rupture of the left main bronchus with left lung atelectasis due to blunt chest injury: a case report - Bi, Taiyu; Duan, Xiaotian (Frontiers in Medicine, 2024)
Background: Bronchial injury is rare in blunt chest trauma, but can be life-threatening. The symptoms of patients with complete bronchial rupture are typical, and most of them are diagnosed in a timely manner and treated with surgery. However, for those with partial rupture of the bronchus, the symptoms are mild, the imaging results are negative, the possibility of delayed diagnosis is high, and serious complications can occur. Early diagnosis and treatment are key to treating this disease. Case description: We report a 52-year-old woman with mild mediastinal emphysema after blunt chest trauma. Left whole-lung atelectasis appeared after a period of conservative treatment. Bronchoscopy revealed injury of the left main bronchus, and surgery was performed. The patient’s lungs recovered well after surgery. CT (Computed tomography) examination during follow-up revealed that the structure of the left main bronchus was intact and unobstructed. The left lung was well recovered. Conclusion: For patients with mild symptoms of blunt chest trauma, mediastinal emphysema and subcutaneous emphysema ; no pleural effusion or pneumothorax ; and a negative chest CT, laryngoscopy or bronchoscopy should be performed in a timely manner to ensure the stability of the respiratory and circulatory system and confirm whether there is tracheobronchial injury. Surgical treatment should be performed in a timely manner after localization and diagnosis.